RIS for 5G and Beyond: A Bibliometric Survey - Yusrina Sabila, Liya; Hayati, Puteri; Warnaningtyas, Murtiatmi; Irene Mulya Irawati , Flaurencia (The Indonesian Institute of Science and Technology Research, 2024)
The rapid advancement of 5G technology has sparked significant interest and investment in research and development across various domains. As the world transitions towards the era of 5G and beyond, understanding the research landscape becomes imperative for guiding future innovations and investments. This article presents a comprehensive bibliometric survey of research in the realm of reconfigurable intelligent surface (RIS) for 5G and its evolutionary successors. Through systematic analysis of scholarly publications, this survey maps the trends, key contributors, influential works, and emerging themes within the field. By synthesizing data from diverse sources, including academic journals and conference proceedings, this survey offers insights into the evolution of RIS technologies, identifies prominent research clusters, and outlines potential directions for future investigation. Furthermore, it sheds light on the interdisciplinary nature of RIS research, spanning areas such as telecommunications, signal processing, antenna design, and network optimization. This bibliometric survey serves as a valuable resource for researchers and practitioners to navigate the complex landscape of 5G innovation and shape the trajectory of future wireless communication systems.